Модель формування готовності курсових офіцерів до виховної роботи з курсантами ВНЗ МВС України - Червоний, П. Д.; Chervonyi, P. D.; ORCID: http://orcid.org/0000-0002-8172-7732 (Педагогіка формування творчої особистості у вищій і загальноосвіт- ній школах : зб. наук. пр. / [редкол.: Т. І. Сущенко (голов. ред.) та ін.]. – Запоріжжя : КПУ, 2015. – Вип. 40 (93). – С. 330-336., 2015)
У статті запропоновано модель формування готовності курсових офіцерів до виховної роботи з курсантами ВНЗ МВС України. Модель ґрунтується на принципах науковості, суб’єкт-суб’єктної взаємодії, особистісної орієнтації, превентивності, суб’єктності, системності (цілісності). Визначено найбільш суттєві підходи виховної роботи: діяльнісний, особистісний, компетентнісний, соціоцентричний, андрагогічний та акмеологічний. Структурними компонентами готовності до виховної роботи з курсантами визначено мотиваційний, гностичний, орієнтаційно-цільовий, комунікативний, конфліктологічний, вольовий. Педагогічну модель реалізовано в три етапи: пропедевтично-діагностувальний, репродуктивно-діяльнісний, рефлексивно-корегувальний.

The article offers a model offorming course officers’ readiness for educational work with cadets of higher educational institutions of the MIA of Ukraine. The model developed consists of the purpose, task, principles, approaches, structural components, preparation contents, stages, tasks of stages, pedagogical conditions, forms and methods of teaching, criteria and indicators, as well as operations in accumulating organizational, communicative, conflictological knowledge, abilities and skills, their application in accordance with the purpose set; psychological and pedagogical knowledge transfer; control of one’s own behaviour, control of emotions, mood; pedagogical communication abilities, speech technique and ability to influence cadet’s personality and cadets collective body. The task of the model is to form a set of knowledge, abilities and skills required to perform educational work with cadets; to develop professionally significant personality qualities (capacity for compromise and cooperation, communicative and organizational abilities, assertiveness). The model is based on the principle of scientific character, subject-to-subject interaction, personality orientation, prevention, subjectiveness, systemic character (integrity). The most essential approaches have been defined: activity, personality, competence, sociocentric, andragogical and acmeological ones. The structural elements of the readiness to perform educational work with cadets have been defined as a motivational, a gnostic, an orientation-purpose, a communicative, a conflictological, a volitional ones.

В статье предложена модель формирования готовности курсовых офицеров к воспитательной работе с курсантами ВУЗ МВД Украины. Модель основывается на принципах научности, субъект-субъектного взаимодействия, личностной ориентации, превентивности, субъектности, системности (целостности). Определены наиболее существенные подходы: деятельностный, личностный, компетентностный, социоцентрический, андрагогический и акмеологический. Структурными компонентами готовности к воспитательной работе с курсантами определены мотивационный, гностический, ориентационно-целевой, коммуникативный, конфликтологический, волевой. Педагогическую модель реализовано в три этапа: пропедевтическо-диагностический, репродуктивно-деятельностный, рефлексивно-корректирующий.
Model of Forming Course Officers’ Readiness for Educational Work with Cadets of Higher Educational Institutions of the Ministry of Internal Affairs of Ukraine
Модель формирования готовности курсовых офицеров к воспитательной роботе с курсантами ВУЗ МВД Украины
Червоний, П. Д. Модель формування готовності курсових офіцерів до виховної роботи з курсантами ВНЗ МВС України / П. Д. Червоний //Педагогіка формування творчої особистості у вищій і загальноосвітній школах : зб. наук. пр. / [редкол.: Т. І. Сущенко (голов. ред.) та ін.]. – Запоріжжя : КПУ, 2015. – Вип. 40 (93). – С. 330-336.
Червоний П. Д. "Модель формування готовності курсових офіцерів до виховної роботи з курсантами ВНЗ МВС України." Педагогіка формування творчої особистості у вищій і загальноосвітній школах 40 (2015): 330-336.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Internal Affairs Agencies; органы внутренних дел; готовность к воспитательной работе; готовність до виховної роботи; воспитательная работа; виховна робота; курсант вищого навчального закладу; курсант высшего учебного заведения; cadets of a higher educational establishment; educational work